Hubungan Citra Tubuh dan Harga Diri dengan Kepercayaan Diri Remaja di SMA Negeri 1 Gading Rejo Pringsewu - Daralita, Gede Arta; Agustriyani, Feri; Damayanti, Rika; Probo, Wisnu; Mukhlis, Hamid (Penerbit Goodwood, 2023)
Purpose: Adolescence is a critical developmental phase marked by physical and psychosocial changes that may affect body image, self-esteem, and self-confidence. This study investigates the relationship between body image and self-esteem with adolescent self-confidence at SMA Negeri 1 Gading Rejo. Research methodology: A quantitative cross-sectional design was employed involving 77 Grade XI students selected through simple random sampling. Data were collected using standardized scales for body image (12 items), self-esteem (10 items), and self-confidence (16 items). The Gamma test was used for statistical analysis. Results: Findings indicate a significant positive correlation between body image and self-confidence (p = 0.006), and between self-esteem and self-confidence (p = 0.000). Most respondents reported moderate levels of body image (79.2%), self-esteem (74.0%), and self-confidence (83.1%), suggesting that positive self-perception contributes to higher confidence. Conclusions: Positive body image and high self-esteem are associated with increased self-confidence among adolescents. Limitations: The study was limited to a single school with a relatively small sample size and a cross-sectional design, which restricts causal inference. Contribution: The research provides empirical evidence on factors influencing adolescent confidence, offering insights for educators and counselors to develop mental health and self-acceptance programs in school settings.